Validation of the Alcohol Use Questionnaire (AUQ) in the Italian Context: A Measure for Assessing Alcohol Intake and Binge Drinking - Eleonora Topino; Alessio Gori (European Journal of Investigation in Health, Psychology and Education, 2025)
An accurate assessment of alcohol consumption is essential for identifying at-risk individuals and informing prevention and intervention strategies. The present study aimed to validate the Italian version of the Alcohol Use Questionnaire (AUQ), a self-report instrument designed to assess both general alcohol intake and binge drinking patterns. A sample of 378 Italian participants (54.5% female; Mage = 26.76 years, SD = 8.44) completed the AUQ along with additional measures assessing binge eating and psychological vulnerabilities related to addiction. Confirmatory factor analysis supported a bifactor model reflecting two distinct but related dimensions: general intake and binge drinking. Network analysis highlighted the central role of perceived frequency of intoxication within the structure of alcohol-related behaviors. Both AUQ indices showed good internal consistency and significant associations with external variables, particularly impulsivity, dissociation, and affect dysregulation, supporting construct validity. The Italian AUQ emerges as a valid and reliable tool for assessing alcohol use patterns and may be useful in both research and clinical practice.